2015
DOI: 10.1371/journal.pone.0138140
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inactive States of Tetrodotoxin-Sensitive Sodium Channels Reduces Spontaneous Firing of C-Fiber Nociceptors and Produces Analgesia in Formalin and Complete Freund’s Adjuvant Models of Pain

Abstract: While genetic evidence shows that the Nav1.7 voltage-gated sodium ion channel is a key regulator of pain, it is unclear exactly how Nav1.7 governs neuronal firing and what biophysical, physiological, and distribution properties of a pharmacological Nav1.7 inhibitor are required to produce analgesia. Here we characterize a series of aminotriazine inhibitors of Nav1.7 in vitro and in rodent models of pain and test the effects of the previously reported “compound 52” aminotriazine inhibitor on the spiking propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Our findings are consistent with reports that poorly selective or Na V 1.7-prefering small-molecule antagonists can block spontaneous or evoked pain responses in preclinical species (Brochu et al, 2006;Haroutounian et al, 2014;Matson et al, 2015;Alexandrou et al, 2016;Deuis et al, 2016;Focken et al, 2016;Frost et al, 2016;Hockley et al, 2017). Clinically, a small cohort of individuals with Na V 1.7 gain-of-function mutations causing inherited erythromelalgia exhibited lower pain scores in response to thermal challenge after short-term dosing with a sulfonamide antagonist (Cao et al, 2016).…”
Section: Methodssupporting
confidence: 91%
“…Our findings are consistent with reports that poorly selective or Na V 1.7-prefering small-molecule antagonists can block spontaneous or evoked pain responses in preclinical species (Brochu et al, 2006;Haroutounian et al, 2014;Matson et al, 2015;Alexandrou et al, 2016;Deuis et al, 2016;Focken et al, 2016;Frost et al, 2016;Hockley et al, 2017). Clinically, a small cohort of individuals with Na V 1.7 gain-of-function mutations causing inherited erythromelalgia exhibited lower pain scores in response to thermal challenge after short-term dosing with a sulfonamide antagonist (Cao et al, 2016).…”
Section: Methodssupporting
confidence: 91%
“…In addition to the aforementioned molecules implicated in ADS, there are many other ion channels/receptors whose expression, location, and/or function can be altered by inflammation ( Gold and Gebhart, 2010 ) and may contribute to altered ADS. Furthermore, previous studies have reported CFA inflammation induced changes in C fiber nociceptor excitability, including increased CV combined with reduced electrical thresholds in guinea pig ( Djouhri and Lawson, 2001 ) not replicated in this or other rat studies ( Baba et al, 1999 ; Nakatsuka et al, 2000 ; Torsney, 2011 ), altered action potential shape ( Djouhri and Lawson, 1999 ; Zhang et al, 2012 ), and spontaneous firing ( Djouhri et al, 2006 ; Xiao and Bennett, 2007 ; Matson et al, 2015 ). Moreover, estrogen exacerbates inflammation-increased excitability of temporomandibular joint afferents ( Flake et al, 2005 ), and there are sex differences in inflammatory sensitization of dural afferents ( Scheff and Gold, 2011 ).…”
Section: Discussionmentioning
confidence: 48%
“…Rats and mice are used widely in efficacy and toxicity assessment during drug development. Given that rat and mouse Nav1.9 share only 76% identity to human Nav1.9 and there are increasing reports of differential Nav channel pharmacology for species orthologs [ 27 , 28 ] we constructed stable cell lines and characterized rat and mouse species orthologs of the channel. Employing the same strategy used for human Nav1.9, rat and mouse Nav1.9 stable cell lines were generated by coexpressing the alpha subunit relevant species versions of β1 and β2 subunits.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that potency for Nav1.9 inhibition by other local anesthetic-like sodium channel blockers like benzocaine, lidocaine, and mexiletine are also reduced by this mutation. Although TC-N 1752 is a known sodium channel inhibitor [ 28 , 36 ] it is structurally quite distinct from local anesthetic like agents and its site of interaction has not yet been defined. Our finding in the current study that the inhibitory activity of TC-N 1752 was essentially abolished by the F1592A/Y1599A mutation strongly suggests an interaction of this agent with the canonical local anesthetic binding site.…”
Section: Discussion/conclusionmentioning
confidence: 99%